Caracterização de remodelação cardíaca em modelo experimental de obesidade a partir de diferentes tipos de dietas hipercalóricas - Matias, Amanda Martins (2017)
Obesity is a worldwide epidemic and a serious public health problem. Several diseases are associated with excess of adipose tissue, and obesity is considered an independent risk factor for the development of cardiac remodeling and heart failure. The objective of the present study was the development and characterization of an obesity experimental model from hypercaloric diets, a high sucrose (HS), high fat (HF) and high fat and sucrose (HFS), which resulted in cardiac remodeling and predisposition to heart failure. The hypothesis of this investigation was that hypercaloric diets would promote cardiac remodeling, cardiovascular damage and predispose to heart failure, being this condition more evident in the high fat and sucrose model. Wistar rats (n = 60) were randomized into four groups: control (C), high sucrose (HS), high fat (HF) and high fat and sucrose (HFS). General characteristics and comorbidities were measured. The process of cardiac remodeling was evaluated through the weights of the heart, left and right ventricles, atrium, and relationships with the tibia length. The mycoyte cross sectional area and fraction of interstitial collagen of the left ventricle were evaluated. In vivo functional evaluation was determined by hemodynamic and in vitro by analysis of isolated cardiomyocyte. Heart failure was analyzed by pulmonary congestion, right ventricular hypertrophy, and hemodynamic parameters. Data were expressed by mean and standard error of the mean and were submitted to analysis of variance (ANOVA) for independent samples. HF and HFS models led to obesity by increase in adipose tissue deposition and adiposity index (C = 8.3 ± 0.2%, HF = 10.9 ± 0.5%, HFS = 10.2 ± 0.3%, p <0.05). Comorbidities were hypertension, glucose intolerance (HF and HFS) and hyperleptinemia (HF). There was no change in the morphological parameters that characterize the cardiac remodeling process. Regarding the functional analyzes, the obesity promotes reduction in time to 50% of shortening (C = 160 ± 4 ms vs. HF = 134 ± 2, p <0.05) and time to 50% of the relaxation (C: 160 ± 4 ms, HF: 134 ± 3 and HFS: 133 ± 3, p <0.05). The HS model presented contractile dysfunction visualized by reduction in the shortening (C: 8.34 ± 0.32%, HS: 6.91 ± 0.28, p <0.05) and maximal shortening velocity (C: -2, 58 ± 0.10 μm / s, HS: -2.21 ± 0.08, p <0.05). In conclusion, the experimental models proposed in this study were not promote cadiac remodeling and predisposition to heart failure under conditions of obesity or sucrose excess.